2014
DOI: 10.5090/kjtcs.2014.47.4.333
|View full text |Cite
|
Sign up to set email alerts
|

Valved Conduit with Glutaraldehyde-Fixed Bovine Pericardium Treated by Anticalcification Protocol

Abstract: BackgroundA preclinical study was conducted for evaluating a valved conduit manufactured with a glutaraldehyde (GA)-fixed bovine pericardium treated using an anticalcification protocol.MethodsBovine pericardia were decellularized, fixed with GA in an organic solvent, and detoxified. We prepared a valved conduit using these bovine pericardia and a specially designed mold. The valved conduit was placed under in vitro circulation by using a mock circulation model, and the durability under mechanical stress was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(45 reference statements)
1
7
0
1
Order By: Relevance
“…Overall, amino acid treatment improved chondrocyte adhesion and proliferation when cultured on a composite scaffold that contains natural materials such as collagen and chitosan. Amino acids played a key role in chondrocyte attachment and proliferation by neutralizing GA cytotoxicity, which guarantees the use of GA as a cross‐linker to consolidate the structural integrity of the designed chitosan‐coated collagen scaffold . This is consistent with the work of Lee et al, in which they used glycine for the detoxification and anti‐calcification of bovine pericardium, as well as with the work of Takahata et al highlighting the proliferation of chondrocytes in the presence of amino acids such as glycine .…”
Section: Resultssupporting
confidence: 83%
“…Overall, amino acid treatment improved chondrocyte adhesion and proliferation when cultured on a composite scaffold that contains natural materials such as collagen and chitosan. Amino acids played a key role in chondrocyte attachment and proliferation by neutralizing GA cytotoxicity, which guarantees the use of GA as a cross‐linker to consolidate the structural integrity of the designed chitosan‐coated collagen scaffold . This is consistent with the work of Lee et al, in which they used glycine for the detoxification and anti‐calcification of bovine pericardium, as well as with the work of Takahata et al highlighting the proliferation of chondrocytes in the presence of amino acids such as glycine .…”
Section: Resultssupporting
confidence: 83%
“…The increased cytotoxicity is possibly due to the unreacted aldehyde groups in GTA that are known to induce some toxicity. [36] In most in vitro tests for drug and gene delivery, [33,37,38] the LDH concentration is normally in the range of 10-100 µg/ml. Thus this toxicity test has demonstrated that the BSA-LDH-GTA delivery platform has negligible toxicity for SMCs and the cancer cell line MCF-7 in our in vitro assay.…”
Section: Cytotoxicity Of Bsa-ldh-gtamentioning
confidence: 99%
“…Indeed, PAA treatment has been reported to have an oxidizing action against the cell membrane and viral capsid, thus providing bactericidal, fungicidal, virucidal and sporicidal properties [18]. It has been applied to several tissues as tendon, skin, heart valves, pericardium and xenogeneic ECM based on small intestine submucosa and urinary bladder matrix, often with altering effects on ECM components and/or other tissue properties [23][24][25][26][27][28][29][30]. Lomas et al have shown that these deleterious effects on tissue ECM might be reduced according to the concentration of PAA applied [24].…”
Section: Introductionmentioning
confidence: 99%